2019
DOI: 10.1103/physrevfluids.4.094603
|View full text |Cite
|
Sign up to set email alerts
|

Pair dispersion in inhomogeneous turbulent thermal convection

Abstract: Due to large scale flow inhomogeneities and the effects of temperature, turbulence small-scale structure in thermal convection is still an active field of investigation, especially considering sophisticated Lagrangian statistics. Here we experimentally study Lagrangian pair dispersion (one of the canonical problems of Lagrangian turbulence) in a Rayleigh-Bénard convection cell. A sufficiently high temperature difference is imposed on a horizontal layer of fluid to observe a turbulent flow. We perform Lagrangia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Recently, Liot et al (2019) have shown that the ballistic approach of Bourgoin (2015) ( § 2.2) can yield a r 0 -dependent intermediate range consistent with observations and the present model. A t 3 scaling was obtained for r 0 /η ≈ 4, while other initial separations approached t 3 scaling from above or below.…”
Section: The Intermediate Range As a Transition Regionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, Liot et al (2019) have shown that the ballistic approach of Bourgoin (2015) ( § 2.2) can yield a r 0 -dependent intermediate range consistent with observations and the present model. A t 3 scaling was obtained for r 0 /η ≈ 4, while other initial separations approached t 3 scaling from above or below.…”
Section: The Intermediate Range As a Transition Regionsupporting
confidence: 89%
“…Dou et al 2018;Petersen, Baker & Coletti 2019), which is limiting when looking for a Richardson scaling regime. There is some evidence to suggest that in Rayleigh-Bénard convection, a t 3 -scaling range also appears for r 0 ≈ 4η with other r 0 approaching from above or below (Liot et al 2019). Pair dispersion experiments at much higher Reynolds numbers would be of considerable interest.…”
Section: Results From Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018), Liot et al. (2019) and Ni & Xia (2013). The collapse of the data at short times using the longitudinal structure function is important since it confirms that is the appropriate velocity scale for the separation of particles at a distance .…”
Section: Regimes Of Pair Dispersion and A Scale-dependent Diffusivitymentioning
confidence: 98%
“…Recent studies further examined buoyancy-driven flows (Schumacher 2008; Ni & Xia 2013; Liot et al. 2019) and pair dispersion of inertial particles (Pitton et al. 2012) or in other complex flows, such as in the stroke of a swimming jellyfish (Kim & Chamorro 2019).…”
Section: Introductionmentioning
confidence: 99%